Non vertical ionization-dissociation model for strong IR induced dissociation dynamics of $${D_{2}}O^{2+}$$ - Jun Wang; Shu Ning Gao; Aihua Liu; Lanhai He; Xi Zhao (Scientific Reports)
Abstract Electron-nuclear coupling plays a crucial role in strong laser induced molecular dissociation dynamics. The interplay between electronic and nuclear degrees of freedom determines the pathways and outcomes of molecular fragmentation. However, a full quantum mechanical treatment of electron-nuclear dynamics is computationally intensive. In this work, we have developed a Strong Laser Induced non-adiabatic Multi-Ionic-Multi-Electric States (SLIMIMES) approach, which contains the electron-laser and electron-nuclear couplings. We validate our model using a showcase example: water dissociation under strong infrared (IR) laser pulses. Our investigation reveals the predominant role of a non-vertical dissociation pathway in the photo-ionization dissociation (PID) process of $$\mathrm {D_{2}O^{2+}}$$ . This pathway originates from neutral $$\mathrm {D_{2}O}$$ , which undergoes vertical multi-photon-single-ionization, reaching the intermediate dissociation states of $$\mathrm {D_{I} + OD_{II}^{+} (2^{3}Σ )}$$ within $$\mathrm {D_{2}O^{+}}$$ . Subsequently, $$\mathrm {OD_{II}^{+} (2^{3}Σ )}$$ dissociates into $$\mathrm {O^{+} + D_{II}}$$ , with both $$\mathrm {D_{I}}$$ and $$\mathrm {D_{II}}$$ fragments potentially ionizing an electron during interaction with the IR laser. This sequential PID pathway significantly contributes to the dissociation yields of water dication. Our calculations are consistent with recent experimental data, which focus on measuring the branching ratio of water dication dissociation. We aim for our model to provide a deeper understanding and a fresh perspective on the coupling between electron and nuclear dynamics induced by a strong IR laser field.